2000
DOI: 10.1093/humrep/15.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome and deliveries following laparoscopic myomectomy

Abstract: Uterine rupture after myomectomy by laparotomy is not a common occurrence. Some case reports of uterine rupture after laparoscopic myomectomy (LM) raise the question of the quality of the uterine scar produced when this technique is performed. In order to assess the outcome of pregnancies and deliveries after LM and to assess the risk of uterine rupture, we performed an observational study. Questionnaires were mailed to all women who had had LM for at least one intramural or subserosal myoma of more than 20 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
142
1
21

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(175 citation statements)
references
References 34 publications
4
142
1
21
Order By: Relevance
“…Increased adhesion formation has also been described following this procedure (16). Furthermore, several authors (17)(18)(19) have also reported cases of uterine rupture/dehiscence following LM. More attention should be paid to careful uterine repair following this laparoscopic procedure.…”
Section: Reconstructive Laparoscopic Myomectomy (Lm)mentioning
confidence: 95%
“…Increased adhesion formation has also been described following this procedure (16). Furthermore, several authors (17)(18)(19) have also reported cases of uterine rupture/dehiscence following LM. More attention should be paid to careful uterine repair following this laparoscopic procedure.…”
Section: Reconstructive Laparoscopic Myomectomy (Lm)mentioning
confidence: 95%
“…1 However, when pregnancy is desired, the technique appears particularly advantageous in that it could reduce the risk of postoperative adhesions compared with laparotomy. [18][19][20] Uterine rupture and abnormal placentation have been cited as possible complications following myomectomy due to weakening of myometrial integrity. The rate of uterine rupture after abdominal myomectomy has been estimated as <1% in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…21 Other studies have demonstrated a 0 to 1% risk of uterine rupture following laparoscopic myomectomy. 20,[22][23] Similarly, the rate of uterine rupture following RALM has been reported anywhere between 0 to 1.1%. 24,25 Since we first began to perform RALM in our institution, we have maintained a database concerning patient outcomes after undergoing this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic myomectomy, rather than abdominal myomectomy, is naturally favoured by patients because it is less invasive and requires a shorter recovery time [1]. Myomectomy is less desirable for women who wish to avoid the possibility of conversion to hysterectomy and who desire a safe pregnancy without a risk of uterine rupture [2][3][4].…”
Section: Introductionmentioning
confidence: 99%